Local Attitudes and Perceptions Toward Large Carnivores in a Human-Dominated Landscape of Northern Tanzania. Issue 4 (4th July 2017) - Mkonyi, Felix J.; Estes, Anna B.; Msuha, Maurus J.; Lichtenfeld, Laly L.; Durant, Sarah M.
ABSTRACT: We conducted 300 semi-structured interviews with local people adjacent to Tarangire National Park, northern Tanzania, to determine their attitudes and perceptions toward large carnivores. We analyzed the relationships between attitudes and age, gender, education, occupation, years at residence, income, distance from protected area, livestock owned, livestock lost to predators and knowledge of carnivores. Three-quarters of respondents (79%) held negative attitudes toward large carnivores, while 20% were generally positive. Three variables were positively associated with attitudes towards different species: formal education (all carnivore species), years at residence (lions and cheetahs), and knowledge of carnivores (cheetahs). Attitudes toward large carnivores were not significantly related to distance from protected area, livestock owned. or livestock lost to predators. Findings suggested that interventions aimed at fostering positive attitudes toward large carnivores should focus on improving formal education and securing long-term residency for people in the region.